Scenic Presence: three architectural investigations in the Archipelago of Gothenburg. - Eliasson, Amanda (My University, 2021)
Understanding of place is a fundamental aspect of the architectural practice. It is a versatile subject of countless layers. The purpose of this thesis is to investigate a part of those layers. Focus is put upon how one can work with the natural prerequisites of a location, and in turn, how an architectural design may answer to the attributes of a landscape. Within the topic, a question is raised regarding what tools could be used to improve the connection towards immediate surroundings and topography in the design process. The investigation takes place at a scenic location in the Gothenburg archipelago. Three situations along the hiking trail of Galterö are explored through addition of structures. These situations represent different typologies of landscapes, where a discussion can be held by comparing how one can answer to different situations within one geographic location. To work with the topography of each situation consciously, the technique of drones and photogrammetry is implemented as a method to achieve highly detailed 3D models, along with on-site investigations. Parallel to this, literature and reference projects on the subject of architecture concerning landscape and identity are studied. Within the direction of building tectonics, the task has been to produce a design that ties the three structures together through a structural concept that suits its purpose, while still offering enough freedom to tailor each piece to the specific situation. In summary, this thesis aims to find strategies and knowledge on how to create thoughtful and qualitative spaces, by gaining an understanding of the given prerequisites of a location.
Keywords: Galterö, topography drone photogrammetry semi-outdoor space, drawings